2014
DOI: 10.1007/s00406-014-0525-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased entropy modulation of EEG response to novelty and relevance in schizophrenia during a P300 task

Abstract: The analysis of the interaction between novelty and relevance may be of interest to test the aberrant salience hypothesis of schizophrenia (SCH). In comparison with other neuroimaging techniques, such as functional magnetic resonance imaging, electroencephalography (EEG) provides high temporal resolution. Therefore, EEG is useful to analyze transient dynamics in neural activity, even in the range of milliseconds. In this study, EEG activity from 31 patients with SCH and 38 controls was analyzed using Shannon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 43 publications
6
37
2
1
Order By: Relevance
“…In contrast, P3b seems to be related to conscious top-down target processing, likely contributing to processing the stimulus information and performing cognitive response (Polich, 2007;Strobel et al, 2008). In previous reports, we found a blunted ERP modulation in Sz as response to both target (Bachiller et al, 2014) and distractor (Bachiller et al, 2015b) tones during an oddball paradigm. Thus, the analysis of the differences in neural pattern generators between Sz patients and healthy controls becomes an interesting research topic to clarify the neural substrate of reduced P300 amplitude in Sz.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…In contrast, P3b seems to be related to conscious top-down target processing, likely contributing to processing the stimulus information and performing cognitive response (Polich, 2007;Strobel et al, 2008). In previous reports, we found a blunted ERP modulation in Sz as response to both target (Bachiller et al, 2014) and distractor (Bachiller et al, 2015b) tones during an oddball paradigm. Thus, the analysis of the differences in neural pattern generators between Sz patients and healthy controls becomes an interesting research topic to clarify the neural substrate of reduced P300 amplitude in Sz.…”
contrasting
confidence: 47%
“…Controls were initially assessed by a semi-structured psychiatric interview to discard major psychiatric antecedents and treatments. Detailed description of treatments and doses, as well as exclusion criteria are detailed in previous reports (Bachiller et al, 2015a;Bachiller et al, 2015b). Symptoms were scored using the Positive and Negative Syndrome Scale (PANSS) (Kay et al, 1987).…”
Section: Subjectsmentioning
confidence: 99%
“…Distractor tones usually have the same frequency of occurrence as target tones. As subjects are asked to respond to target tones, distractor tones only possess a novelty component, while target tones are associated to both novelty and relevance [12]. Several methods have been used to analyze transient dynamics in neural activity during an auditory oddball task or during resting-state.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to analyze transient dynamics in neural activity during an auditory oddball task or during resting-state. Such measures, of a time-dependent nature, include wavelet entropy [6,13], multiscale entropy [14], median frequency [12,15] and relative power (RP) [15], among others. Many of these studies have found widespread lower neural reorganization (i.e., transient dynamical reorganization of brain activity during an attentional process) for SCH subjects compared to controls during the active task response [6,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…P. Núñez was in receipt of a 'Promoción de empleo joven e implantación de la Garantía Juvenil en I+D+i' grant from 'Ministerio de Economía y Competitividad' and the University of Valladolid, J. Gomez-Pilar and A. Bachiller (i.e., a subcomponent of P300, a positive going-amplitude that peaks around 300 ms after a relevant stimulus) [5].…”
Section: Introductionmentioning
confidence: 99%